Umbrales: A Collection of Poetry in Spanish - Allen J Zegarra Acevedo (Vernacular: New Connections in Language, Literature, & Culture, 2022)
De la nada, Mi reino, El encargo, Ser, and Desde mi ventana are the first five poems of an unpublished collection entitled Umbrales. These poems explore the dilemmas that human beings usually face, primarily, in the early stages of life. Finding yourself and questioning your willingness to break free from others’ expectations is at the core of “Umbrales”.